PENDAMPINGAN INOVASI PRODUK DAN DIGITALISASI PEMASARAN UNTUK MENINGKATKAN DAYA SAING UMKM KRIPIK TEMPE LEK JA'IM - Azhari; Edy Suhartono; Della Puji Setyorini; Allisya Syifa Al'Haidar (Jurnal Abdi Masyarakat, 2026)
MSMEs play a vital role in the national economy, yet many still face challenges in business development and digital marketing adoption. The Lek Ja'im Tempe Chips MSME in Ngampel Village, Kapas District, Bojonegoro Regency, has strong local product potential but has not fully utilized product innovation and digital marketing to enhance competitiveness. This community service program aimed to improve business competitiveness through product innovation and digital marketing assistance using a participatory learning-by-doing approach. Activities included product diversification, packaging improvement, branding, and the establishment of digital marketing channels through TikTok and Shopee. The program increased product variants from one to four flavors, established one TikTok business account and one Shopee store, published two promotional contents, increased monthly customers from 75 to 100 (33.3%), and raised monthly turnover from IDR 2,000,000 to IDR 4,500,000 (125%). These findings demonstrate that the program effectively strengthened business capacity and competitiveness while providing a practical model for sustainable MSME empowerment